Perihal Aspektualitas dan Sistem Kala dalam Bahasa Jepang: Suatu Kajian Morfologi dan Semantik - Titien Rostini (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2011)
Semantically, aspectuality and temporality (tenses) are associated with the element of time : tense is related with two points which is, temporal reference point and temporal point of situation in deictic character. Aspectuality only reffering to time from the situation (beginning, the initial progress or at the end of a situation that is nondeictic).In the Japanese language as well, aspectuality and the tenses as a functional semantic category refers to situations when the element internal / external may be disclosed through the disclosure of internal variability in the morphology and functional context in syntax level.In a Japanese sentence is often found common ground between aspectuality and aspectuality. Therefore, there should be a scientific explanation of various events and aspectuality of the tenses in Japanese.